Imperial Silver Laundering: The Official Narrative on Gold Floral Silver and the Silverization of Ming State Finance. (3rd July 2017) - Grass, Noa
Abstract : Ming China completed its transition to a silver economy when the government endorsed silver as its primary means of payment. According to the official narrative, this happened in 1436 when the grain tribute tax, the financial base of the imperial house and central government, was commuted into the precious metal under the title of gold floral silver. Relying on material and textual evidence, this paper challenges this narrative. It shows that the term gold floral silver did not officially appear in this context before the sixteenth century and argues that its appearance reflects a deep transformation in fiscal policy. In the official narrative, historical information was edited to mask this break and legitimize it. By doing so, a seemingly technical administrative text served as a means for realizing governmental change in a political culture that did not create any legal avenues to do so.